2019
DOI: 10.14256/jce.2728.2019
|View full text |Cite
|
Sign up to set email alerts
|

Examples of trends in water management systems under influence of modern technologies

Abstract: Examples of trends in water management systems under influence of modern technologiesReliable and timely information about the current and future condition of water enables an efficient management of water management systems. Advantages and challenges of the use of modern technologies in the collection, analysis, and integration of data, are presented in this paper by means of several examples of water management systems. It is shown how advanced technologies demonstrate a pronounced efficiency in accurate mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Al-Saady et al [29] also showed that the use of remotely sensed data (ASTER GDEM) and GIS techniques (ArcSWAT and other GIS tools) is more appropriate, precise, and economic for extracting drainage network and morphometric parameters of river basins, compared to traditional methods. GIS techniques are excellent tools for hydrologic analyses of drainage networks and for the high-accuracy drainage basin mapping [29], [30].…”
Section: Geospatial Technology In Agriculturementioning
confidence: 99%
“…Al-Saady et al [29] also showed that the use of remotely sensed data (ASTER GDEM) and GIS techniques (ArcSWAT and other GIS tools) is more appropriate, precise, and economic for extracting drainage network and morphometric parameters of river basins, compared to traditional methods. GIS techniques are excellent tools for hydrologic analyses of drainage networks and for the high-accuracy drainage basin mapping [29], [30].…”
Section: Geospatial Technology In Agriculturementioning
confidence: 99%